(untitled) (Actual Problems of Psychology in Educational Institutions, 2022)
The article is devoted to the analysis of the problem of professional self-determination at the stage of choosing a profession in adolescence. Psychological and pedagogical ideas about the essence and content of professional self-determination are considered. Emphasis is placed on the choice of profession as the main strategic stage of professional self-determination in early adolescence. The description of obstacles of a professional choice is given, the essence of the contradictions arising in the course of a choice of a profession is opened. Emphasis is placed on the main factors that determine the professional choice. It is proved that the determinants of conscious choice of profession are both internal and external factors.